Rapid dispatch for out-of-hospital cardiac arrest is associated with improved survival. (June 2021) - Gnesin, Filip; Møller, Amalie Lykkemark; Mills, Elisabeth Helen Anna; Zylyftari, Nertila; Jensen, Britta; Bøggild, Henrik; Ringgren, Kristian Bundgaard; Blomberg, Stig Nikolaj Fasmer; Christensen, Helle Collatz; Kragholm, Kristian; Lippert, Freddy; Folke, Fredrik; et al.
Abstract: Aim: As proxy for initiation of the first link in the Chain of Survival by the dispatcher, we aimed to investigate the effect of time to first dispatch on 30-day survival among patients with OHCA ultimately receiving the highest-level emergency medical response. Methods: We linked data on all OHCA unwitnessed by emergency medical services (EMS) treated by Copenhagen EMS from 2016 through 2018 to corresponding emergency call records. Among patients receiving highest priority emergency response, we calculated time to dispatch as time from start of call to time of first dispatch. Results: We included 3548 patients with OHCA. Of these, 94.1% received the highest priority response (median time to dispatch 0.84 min, 25th–75th percentile 0.58–1.24 min). Patients with time to dispatch within one minute compared to three or more minutes were more likely to receive bystander cardiopulmonary resuscitation (77.3 vs 54.2%), bystander defibrillation (11.5 vs 6.5%) and defibrillation by emergency medical services (24.1 vs 7.5%) and were 2.6-fold more likely to survive 30 days after the OHCA (P = 0.004). Results from multivariate logistic regression were similar: odds ratio (OR) of survival 0.83 per minute increase (95% confidence interval 0.70–1.00, P = 0.04). However, survival was similar between those who received highest priority response and those who did not: OR of survival 0.88 (95% confidence interval 0.53–1.46, P = 0.61). Conclusion: Rapid time to dispatch among patients with highest priority response was significantly associated with a higher probability of 30-day survival following OHCA.